CONTINUOUS OBSTETRIC CARE (CONTINUITY OF CARE) ON MRS. L WITH THE BREAST MILK DAM AT PMB BD. WANTI MEDAN DELI DISTRICT NORTH SUMATRA PROVINCE YEAR 2025 - Simanjorang, Jenni Murni Wati; Lisa Putri Utami Damanik; Dyanti SR Butarbutar; Lia Andriani; Valentina Lusia Berutu; Amanda Salsyahbillah; Mastina, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are critical health indicators. Perineal rupture is a significant cause of morbidity during childbirth, requiring proper management to prevent hemorrhage and infection. These risks can be mitigated through Continuity of Care (COC). To provide comprehensive midwifery care to Mrs. L, aged 26, covering the third trimester of pregnancy, delivery, newborn care, postpartum, and family planning, utilizing Varney’s management and SOAP documentation. This descriptive study with a case study approach was conducted at PMB Bd. Wanti S.Keb, Medan, in 2024. The subject was a third-trimester pregnant woman monitored through the postpartum period. During pregnancy, Mrs. L experienced physiological back pain, resolved through counseling and exercise. Spontaneous delivery occurred at 41 weeks. A second-degree perineal rupture involving the vaginal mucosa and muscles occurred during the second stage. Management involved continuous suturing and strict monitoring. The female baby was born vigorous with normal vital signs. Postpartum visits confirmed good uterine involution and successful lactation. Continuity of Care was successfully implemented. The management of the second-degree perineal rupture adhered to Normal Childbirth Care standards, effectively preventing complications like hemorrhage or infection.